Cigarette smoking behaviour among medical doctors and psychological symptoms - Tuğlu, Cengiz; Güzelant, Asuman; Erdoğan, Sarper; Şenveli, Bahar; Abay, Ercan (Journal of Dependence, 2000)
One of the important health problems of our time is cigarette smoking which has biological, psyhological and sociocultural associations. Over 80 % of cigarette smokers express their wisher as to get rid of smoking behaviour. It is expected from health workers and especially medical doctors to be leader and to be model to get rid of smoking. For this reason in our study we aimed to examine smoking behaviour, reasons, and its relationship with psychological symptoms on medical doctors who are living in Edirne, among formal health constitutions in Edirne and academic staff of Medical Faculty of Trakya University.